2022
DOI: 10.3390/catal12020122
|View full text |Cite
|
Sign up to set email alerts
|

Study of Influence Factors in the Evaluation of the Performance of a Photocatalytic Fibre Reactor (TiO2/SiO2) for the Removal of Organic Pollutants from Water

Abstract: The performance of a photocatalytic fibre reactor (UBE Chemical Europe), made of cartridges of fine particles of TiO2 dispersed within silicon fibres and irradiated by ultraviolet light, for the removal of organic pollutants from synthetic waters was evaluated. In the sensitivity analysis carried out, the factors catalytic surface area, fibre state, temperature and initial substrate concentration were studied using 4-chlorophenol as a test compound. The percentage of titanium in the fibre remained practically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Findings from various reports for a dilute solution revealed that PCD rate increases along with increasing C P,0 . 34,64,82,83 The recombination time of hole-electron pairs is very short (a few nanoseconds), 84 causing that photo-excited sites only react in a very narrow area. Therefore, a high C P,0 enhances the collision probability between organic molecules and photoexcited sites.…”
Section: Effect Of Other Factorsmentioning
confidence: 99%
“…Findings from various reports for a dilute solution revealed that PCD rate increases along with increasing C P,0 . 34,64,82,83 The recombination time of hole-electron pairs is very short (a few nanoseconds), 84 causing that photo-excited sites only react in a very narrow area. Therefore, a high C P,0 enhances the collision probability between organic molecules and photoexcited sites.…”
Section: Effect Of Other Factorsmentioning
confidence: 99%
“…It should also be noted that most of the studies of Photocatalysis on TiO 2 have been carried out using the suspension of fine particles of the photocatalyst in the solution to be treated. This operation thus has a limit because the fine particles of TiO 2 complicate the filtration once the solution has been treated [9]. As a result, photocatalytic suspension reactors are not compatible with the production of large-scale installations.…”
Section: Introductionmentioning
confidence: 99%
“…[6] However, TiO 2 has its drawbacks affecting reactivity, such as slow reaction rates, low quantum efficiency, and a narrow light absorption range. [7] Based on researches proposed various modification methods, including microelectronic structure modulation, [8] phase and morphology control, [9] crystal facet [10] and defect engineering, [11] construction of homojunction [12] and heterojunction, [13,14] many remarkable results have been achieved. Among them, defect engineering can modulate the electronic properties and photocatalytic reaction performance of TiO 2 by introducing vacancies, [15] which has been extensively investigated due to its low cost, simple preparation, and high efficiency.…”
Section: Introductionmentioning
confidence: 99%